Chemoenzymatic enantioselective synthesis of phenylglycine and phenylglycine amide by direct coupling of the Strecker synthesis with a nitrilase reaction - Eppinger, Erik; Gröning, Janosch Alexander David; Stolz, Andreas (Frontiers in Catalysis, 2022)
The conversion of rac-phenylglycinonitrile by different variants of the nitrilase from Pseudomonas fluorescens EBC191 (EC 3.5.5.1) was studied and the amounts and chiral composition of the formed phenylglycine and phenylglycine amide compared. Muteins that converted rac-phenylglycinonitrile to extraordinarily high amounts of phenylglycine or phenylglycine amide were tested for the chemoenzymatic enantioselective one-pot synthesis of (R)- and (S)-phenylglycine and (R)- and (S)-phenylglycine amide. The chemoenzymatic synthesis combined the initial step in the traditional chemical Strecker synthesis which results in the formation of rac-phenylglycinonitrile from benzaldehyde, cyanide, and ammonia with the enzymatic conversion of the formed nitrile by the nitrilase variants. The aminonitrile synthesis was optimized in order to obtain conditions which allowed under mildly alkaline conditions (pH 9.5) maximal yields of phenylglycinonitrile and the in-situ racemization of the compound. The racemic phenylglycinonitrile was directly converted under the alkaline conditions without any interposed purification step by cells of Escherichia coli overexpressing recombinant nitrilase variants. The application of a mutant of E. coli defect in a (S)-phenylglycine amide hydrolysing peptidase (E. coli JM109ΔpepA) expressing a highly reaction- and (R)-specific nitrilase variant allowed the synthesis of (R)-phenylglycine with ee-values ≥ 95% in yields up to 81% in relation to the initially added benzaldehyde. These yields indicated a dynamic kinetic resolution which involved the racemization of (S)- to (R)-phenylglycinonitrile under the used alkaline conditions with the concurrent hydrolysis of (R)-phenylglycinonitrile to (R)-phenylglycine. The addition of resting cells of E. coli JM109ΔpepA synthesizing an amide forming nitrilase variant to the final product of the Strecker synthesis and/or using E. coli strains with an intact aminopeptidase gene resulted in the preferred formation of (S)-phenylglycine amide, (R)-phenylglycine amide or (S)-phenylglycine.